Hypnotics with novel modes of action. Issue 2 (17th January 2020) - Hoyer, Daniel; Allen, Andrew; Jacobson, Laura H.
Abstract : Insomnia and, more generally, lack of sleep are on the rise. Traditionally treated by classical hypnotics, such as benzodiazepines and Z drugs, which both act on the GABAA receptor, and other modalities, including nondrug therapies, such as cognitive behavioural therapy, there is a range of new hypnotics which are being developed or have recently received market approval. Suvorexant and the like target the orexin/hypocretin system: they should have less side effects in terms of drug–drug interactions with e.g. alcohol, less memory impairment and dependence potential compared to classical hypnotics.